2020
DOI: 10.1111/jcal.12501
|View full text |Cite
|
Sign up to set email alerts
|

Learning immunology in a game: Learning outcomes, the use of player characters, immersion experiences and visual attention distributions

Abstract: This study contributed to the current body of literature on game‐based learning by investigating the way playing an educational game, Humunology, affected learning about the immune system and examining further the association between game immersion and visual attention distribution. A total of 79 undergraduate and graduate students participated, and data were collected both in situ and ex situ. The results showed that the students learned through playing Humunology, and the analyses of the use of player charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…(4) PP refers to students' tendency to interact spontaneously with online learning platforms (Shim & Shim, 2020). Interesting platforms can improve their learning quality and satisfaction, concentrate their attention and deepen their immersive experience (Cheng et al, 2017;Klock et al, 2019;Teng et al, 2021). When students find the online learning platform interesting, they can recognize the learning playfulness, and also helps their online learning positivity and effectiveness.…”
Section: Platform Environment and Learning Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) PP refers to students' tendency to interact spontaneously with online learning platforms (Shim & Shim, 2020). Interesting platforms can improve their learning quality and satisfaction, concentrate their attention and deepen their immersive experience (Cheng et al, 2017;Klock et al, 2019;Teng et al, 2021). When students find the online learning platform interesting, they can recognize the learning playfulness, and also helps their online learning positivity and effectiveness.…”
Section: Platform Environment and Learning Effectivenessmentioning
confidence: 99%
“…Interesting platforms create a relatively active learning atmosphere, further amplifying the learning environment advantages. It can enhance students' willingness to interact, learn and participate (Teng et al, 2021). SE can alleviate students' fear of difficulties and enhance their PU and PEU (Karabacak et al, 2019).…”
Section: Comprehensive Analysis Of Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study investigating the educational effects of anthropology through a GBL approach was carried out to learn about the association between game immersion and visual attention distribution. The eye tracking technology showed that students who played anthropology in an immersive manner were more focused on the played character [86]. In a study of viewers' visual attention to subtitles in home shopping broadcasts, eye tracking technology was used to obtain objective data on visual attention to home shopping subtitles and to determine the factors that draw the visual attention to subtitles on television home shopping screens.…”
Section: Eye Tracking Technology and Visual Attentionmentioning
confidence: 99%
“…Numerous positive outcomes have been linked to welldesigned, robust educational games such as motivation, satisfaction, engagement, joy, captivation, immersion, creativity, and problem-solving (1)(2)(3)(4)(5)(6). Currently, the relationship between flow experience and the mentioned outcomes is under investigation in educational games in higher education, mostly outside the field of medical education (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%